Effect of temperature at various growth stages on seed quality in Brassica species - SUMEET KUMAR SINGH; S.K. CHAKRABARTY; RAKESH PANDEY (Seed Research, 2026)
A field experiment was conducted with eleven rapeseed and Indian mustard varieties grown in 4 dates of sowing in rabi 2011-12 to evaluate the emergence of seeds. The mature seeds of the varieties were collected as and when the varieties matured. The activity of enzymes (peroxidase and catalase) and seed germination at five temperature (20, 25, 30, 35 and 40°C) conditions in the laboratory were recorded. The varieties showed lower germination at 20°C and 35°C in comparison to that in 25°C and 30°Ctemperature while it was nil at 40°C. The seeds maturing at lower temperature in early sowing conditions showed higher seed germination as compared to those matured at higher temperature in case of late sowing conditions. The results also indicated that higher temperature at seed filling and maturity enhanced the enzyme activities. A comparison among early, timely and late sown varieties indicated that timely and late sown varieties had higher activities of peroxidase and catalase enzymes.